Identification of Hotspot and Burned Area in Merauke District, South Papua Province - Silvi Nadia Kirana; Ati Dwi Nurhayati (Jurnal Silvikultur Tropika, 2022)
Papua province is one of fire prone province in Indonesia. Merauke experiences forest and land fires almost every year. The objectives of this study were to identify the distribution of hotspots and burned area in Merauke District, South Papua Province in 2015 and 2019. Hotspot data was obtained from the Terra/Aqua MODIS satellite imagery. Data analysis was carried out by identifying the distribution of hotspots for each type of land cover, as well as identification of burnt areas with buffering hotspots at a distance of 1 km x 1 km. Total number of hotspots in 2015 was 2.671 with 2.611 hotspots on mineral soil and 60 hotspots on peatland area. Total hotspots in 2019 were 534 with 524 hotspots on mineral soil and 10 hotspots on peatland area. The burned area in 2015 was 98% on non-peat land and 2% on peat land of the total burnt area in Merauke Regency. The burnt area in 2019 also occurred 98% on non-peat land and 2% on peatland. The biggest forest and land fires in 2015 and 2019 occurred in the land cover type of swamp scrub. Keywords: burned area, forest fire, hotspot, Merauke District